APLIKASI PEMASARAN PERUMAHAN PT. GRIYA ABEE MAKMUR RAGAJAYA CITAYAM KABUPATEN BOGOR MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT (RAD) BERBASIS WEB - Vramasatya, Muhammad Risqi; Faizah, NM; Nurcahyo, Widyat (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2022)
Housing marketing or commonly known as property marketing is an activity to promote land or a building that will be traded according to the target market to the public. In Indonesia, currently the development of property developer agencies is experiencing rapid progress. Therefore, business competition in the marketing world is becoming more stringent, which forces all companies to improve their quality in order to keep up with the competition. Companies must pay more attention in terms of marketing and service quality which are very important for consumers so that when using the services provided by the company it will be in accordance with their individual needs which can fulfill consumer desires. The author conducts research that aims to design marketing and service applications for ordering houses according to what is needed in order to fulfill customer desires at PT. Griya Abee Makmur Ragajaya Citayam Bogor Regency to replace housing promotion with manual methods such as distributing flyers. Therefore the author created a housing marketing application using the web-based Rapid Application Development method to help PT. Griya Abee Makmur when disseminating information about the houses being bought and sold.